PLANIFICACIÓN BASADA EN PROYECTOS E INCIDENCIA EN EL DESARROLLO ÁULICO: NIVEL BÁSICA SUPERIOR DE LA UNIDAD EDUCATIVA “BOLIVARIANO” - TOBAR MERCADO MARÍA ISABEL (2024)
Education has changed a lot in recent years. Throughout history we have seen several transformations, before a traditional school education was practiced, where the student only learned by memorization and in a very insignificant way. Today, in a changing social context and with great challenges, education has evolved drastically, becoming more meaningful, more comprehensive and where intelligences, cognitive and social skills, competencies and skills are enhanced. In this sense, Andrade, et al. (2017) state that for this purpose it is very important to provide tools and spaces that facilitate the learning of social skills, fostering in students harmonious relationships, aptitudes and skills that will help them throughout their school life. It should be taken into account that it should be analyzed under the perspective of being applied to their needs, without forgetting the interdisciplinary nature of current demands (p.6). . In order to achieve an education with the new paradigmatic approaches, a methodological strategy that has presented great results and that has become essential for the practice within the educational process has been used nowadays. This is the Project Based Learning (PBL) that seeks to develop in students active collaboration skills in situations in a cooperative and collaborative manner that confronts students with situations that require them to work in a collaborative way. Translated with DeepL.com (free version)